Hygiene, Sanitation, and The Contents of Escherichia coli in Ice Cubes at Pasar Malam Kampung Solor, Kupang - Fitria Sry Wahyuni; Agus Setyobudi; Indriati A. Tedju Hinga (Universitas Nusa Cendana, 2021)
Ice cubes are complementary food products that are added to drinks to make them cool and refreshing and are also in great demand by the public. Therefore, the ice cube production process must also meet food safety for the sake of public health. The research design used descriptive observation, to describe or provide an overview of the hygiene and sanitation of ice cube processing, as well as the bacteriological content of ice cubes produced by households at Pasar Malam Kampung Solor by conducting the Most probable Number (MPN) Escherichia coli test. The sample used the purposive sampling technique. Data collection techniques using interviews and observation. The results of this study indicate that the hygiene and sanitation of ice cube processing for the home industry at Pasar Malam Kampung Solor have not met the requirements, seen from the use of raw water, the behavior of handlers, equipment, and unhygienic processing methods. The results of laboratory examinations found that 50% of the ice cube samples were negative and 50% of the ice cube samples were positive containing Escherichia coli bacteria with levels of Escherichia coli bacteria, namely 20 MPN/100 ml and 240 MPN/100 ml (not eligible) or exceeding the threshold > 0 MPN /100 ml according to Permenkes 492/Menkes/PER/IV/2010.